The role of social media in the spread of information - a study on the endeavor expansion between the appearance of texts and the sharia intentions - Yousef A. Baker, El-Ebiary; Ragab Aboumelih, Mohamed Soliman; Ahmed Ramadan, Mohamed Ahmed (The Mattingley Publishing Co., Inc., 2020)
This research sheds light on the importance of social networking programs via the Internet in the circulation and spread of health information and falsehood alike, as well as discusses the dispute that occurred between contemporary jurists about the expansion of the endeavor of Al-Safa and Marwa - casually - and does this expansion fall within the endeavor or not? This expansion took place in two phases. The first stage was expansion through expansion straight through the construction of upper floors, and this took place without denial, and the second stage was carried out through expansion horizontally from the supply side and this is the source of disagreement between the jurists, and this research talks about photographing the issue and editing a place The dispute therein, and the dispute that arose between the jurists, as well as the preponderant opinion and evidence thereof, and the research reached some important results that will be presented at the end of the research.